الأبعاد الاجتماعية والثقافية في رواية حطب سراييفو لسعيد خطيبي - ميرار, دويس, سليمة صنية; بته, محمد (University of El-oued, 2022)
شهدت سنوات التسعينيات من القرن الماضي نمط روائي جديد، نتيجة التحولات السياسية التي مرت بها الجزائر وما نتج عنها من عنف دام، أطلق عليه أدب الأزمة، فكان هذا الأدب والذي اشتركت تيماته عند أدباء المرحلة بمثابة السجل لكل ما حدث في المجتمع الجزائري التسعيني من قتل ودمار وتخريب، وقد جاوزها الروائيون المعاصرون إلى مقارنتها بحروب أهلية وقعت في غير مكان وزمان الذي وقعت فيه حرب الجزائر كرواية حطب سراييفو لسعيد خطيبي، والتي تضمنت مخلفات الحرب الدامية من قلق وخوف وآثار نفسية ومختلف أنواع العنف التي واجهها الأفراد الذين عايشوا تلك الحقبة في كل من الجزائر وسراييفو. The nineties of the last century saw the emergence of a new style of novel called "Literature of the crisis" as a result of the political changes that Algeria has known, and it still remains in use. This kind of literature, of which the novelists of this period share the same themes, is considered to be the minutes of the events experienced by Algerian society in the past as murder, destruction and sabotage. Contemporary novelists have gone so far as to compare these events to civil wars in a place and time other than the Algerian war, like the novel by SaïdKhatibi "The Wood of Sarajevo", which describes the aftermath of the bloody war in Algeria such as anguish, fear, psychological trauma and the different types of violence suffered by individuals who lived this time even in Algeria or in Sarajevo.
Keywords: the Algerian novel; Literature of the crisis; Violence; educated; Sarajevo.; الرواية الجزائرية، الاجتماعي، الثقافي، العنف، سراييفو